The effect of led light sources with varied spectral composition on the in vitro rooting bility of garden strawberry (Fragaria × ananassa) - I. A. Byadovsky (Труды по прикладной ботанике, генетике и селекции)
Consideration is given to the possibility of using LED light sources with different ratios of red (650 - 660 nm), orange (600 - 610 nm) and blue (440 - 450 nm) light in the light flux in the rooting stage of garden strawberry (Fragaria × ananassa (Duch. ex Weston) Duch. ex Rozier) grown in vitro. The study covered a sizable diversity of strawberry cultivars (selected from the in vitro collection): ‘Borovitskaya’, ‘Vityaz’, ‘Zenga Zengana’, ‘Khoney’, ‘Tsaritsa’, ‘Kubata’, ‘Dukat’, ‘Marmalada’, ‘Valenta’, ‘Rusich’, ‘Krasavitsa Zagorya’, ‘Neznakomka’ and ‘Roksana’, thus ensuring quite diversified results. It was established that the use of LED sources with an increased content of red light in the light flux increased the rooting percentage (1.15-1.25 times) and the number of roots per one microcutting (1.29-1.77 times) in in vitro culture, as compared with fluorescent lamp lighting. It was observed that with different spectral compositions of light the rooting ability of microcuttings was cultivar-specific.